2019
DOI: 10.3748/wjg.v25.i40.6145
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in inflammatory bowel disease: Results from the United Kingdom inception epidemiology study

Abstract: BACKGROUNDThe current epidemiology of inflammatory bowel disease (IBD) in the multi-ethnic United Kingdom is unknown. The last incidence study in the United Kingdom was carried out over 20 years ago.AIMTo describe the incidence and phenotype of IBD and distribution within ethnic groups.METHODSAdult patients (> 16 years) with newly diagnosed IBD (fulfilling Copenhagen diagnostic criteria) were prospectively recruited over one year in 5 urban catchment areas with high South Asian population. Patient demographics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 36 publications
2
25
0
1
Order By: Relevance
“…In a recent epidemiologic study in 2016, the incidence of UC in an Indian group was higher (20.5 cases/10 5 /year) than that in a Pakistani group (11.2 cases/10 5 /year) and white European group (7.5 cases/10 5 /year) in the multi-ethic United Kingdom, although the study population was predominantly born in the United Kingdom. 14 Interestingly, the prevalence of CD in the same South Asian community in Leicester city was lower than that in Europeans (33.2 cases/10 5 /year vs. 75.8 cases/10 5 /year, respectively). 12 Indeed, research supports a difference between UC and CD epidemiology in immigrants: early life dysbiosis events, such as caesarean section, increased hygiene, and repeated antibiotics, are related to the risk of CD, whereas late dysbiosis events are related to the risk of UC.…”
Section: Epidemiology Of Ibd In Asian Migrantsmentioning
confidence: 76%
“…In a recent epidemiologic study in 2016, the incidence of UC in an Indian group was higher (20.5 cases/10 5 /year) than that in a Pakistani group (11.2 cases/10 5 /year) and white European group (7.5 cases/10 5 /year) in the multi-ethic United Kingdom, although the study population was predominantly born in the United Kingdom. 14 Interestingly, the prevalence of CD in the same South Asian community in Leicester city was lower than that in Europeans (33.2 cases/10 5 /year vs. 75.8 cases/10 5 /year, respectively). 12 Indeed, research supports a difference between UC and CD epidemiology in immigrants: early life dysbiosis events, such as caesarean section, increased hygiene, and repeated antibiotics, are related to the risk of CD, whereas late dysbiosis events are related to the risk of UC.…”
Section: Epidemiology Of Ibd In Asian Migrantsmentioning
confidence: 76%
“…Twenty-one per cent of this study's participants were from a BAME background and therefore proportionally representative of the UK IBD population in ethnically diverse regions [26]. Compared to their white counterparts, the BAME cohort was less likely to state English as their main language but this did not appear to be a significant barrier to their decision-making as there were no differences in their CRC risk knowledge and they did not report feeling any less TA B L E 3 Thematic analysis of answers given by respondents for reasons why they did not feel well informed…”
Section: Discussionmentioning
confidence: 99%
“…Misra et al (23) found that biological therapy for CD was prescribed signi cantly less often for South Asians compared to British White patients. Heterogeneity in disease phenotype in ethnic minority groups can be in uenced by differential cultural and environmental exposures (e.g., environmental pollutants, smoking and microbial exposure), forming an generational impact (13,23). In the UK, Misra et al (23) found that most second-generation Indians (aged 15 to 40) had higher age-adjusted incidence of UC compared to White Europeans and Pakistanis, indicating that subcultural differences amongst South Asians themselves needs further consideration, and that heightened genetic susceptibility and environmental triggers may promote the risk of developing UC with a non-colonic phenotype for Indian minority patients.…”
Section: Introductionmentioning
confidence: 99%
“…Ethnic minority patients may also receive poor healthcare. Misra et al (23) found that biological therapy for CD was prescribed signi cantly less often for South Asians compared to British White patients. Heterogeneity in disease phenotype in ethnic minority groups can be in uenced by differential cultural and environmental exposures (e.g., environmental pollutants, smoking and microbial exposure), forming an generational impact (13,23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation